Quantifying soil carbon sequestration from regenerative agricultural practices in crops and vineyards - Villat, Jessica; Nicholas, Kimberly A. (Frontiers in Sustainable Food Systems, 2024)
Regenerative agriculture commonly aims to increase soil carbon sequestration, with potential benefits for human and ecosystem health, climate mitigation, and biodiversity. However, the effectiveness of various regenerative practices at increasing carbon sequestration is unclear. This study identified and quantified the yearly soil carbon sequestration rate of regenerative practices in arable cropland and vineyard ecosystems through a literature review. We examined N=345 soil carbon sequestration measures across seven regenerative practicesagroforestry, cover cropping, legume cover cropping, animal integration, non-chemical fertilizer, non-chemical pest management, and no tillage. Our findings indicate that all seven practices effectively increased the carbon sequestration rate. There were no statistically significant differences among the practices. Combining these practices appeared to further enhance soil carbon sequestration. We propose a sequence of regenerative practices that farmers can adopt, balancing ease of implementation and carbon sequestration effectiveness. We suggest further research is needed for under-studied practices, such as long-term monitoring studies and randomized controlled trials in perennial systems, to improve their implementation and effectiveness, and to overcome small sample sizes currently available to quantify carbon sequestration.